Perbaikan Proses Pengiriman Dokumen Purchase Order dan Goods Received Note Menggunakan Value Stream Mapping - M Hudori; Nurul Hasanah (Politeknik Kelapa Sawit Citra Widya Edukasi, 2021)
This research discusses the use of Value Stream Mapping (VSM) to analyze waste in the process of sending Purchase Order (PO) and Goods Received Note (GRN) documents. The purpose of this research is to determine the existence of waste in the flow of the document delivery process and make improvements to the things that cause the waste. This research was conducted on April 2nd - July 14th, 2018 at a distribution company located in Kabupaten Bekasi, West Java. The object of research is focused on the process of sending PO and GRN documents to vendor in the Department of Transportation and Distribution. Data gatering was carried out through observation of object and interview with sources, namely parties related to the object of research. The data analysis method used was VSM analysis with the following steps: 1) making Current State Mapping; 2) calculation of Process Cycle Efficiency (PCE); 3) making Process Activity Mapping (PAM); and 4) making Future State Mapping. The result showed that there were waste activities, ie excess processing, waiting and motion. The proposed improvement concept were: 1) reducing the approval process time; 2) create a procurement checkpoint; 3) eliminates the waiting time for the confirmation process; 4) eliminating waiting time for approval process; 5) eliminating approval; 6) eliminates the process of waiting for delivery of documents to vendors; and 7) establish a FIFO system for document delivery to vendor.